Newtopia : The States of Human Rights. - Gregos, Katerina; Mechelen; Vaneigem, Raoul; Moyn, Samuel; Khatib, Lina; Azoulay, Ariella; Sorokina, Elena; Malik, Kenan; Ebadi, Shirin; San Suu Kyi, Aung; Politkovskaya, Anna; Xiaobo, Liu; et al. (Antwerpen : Ludion, 2012)
Agarwal, Ravi ; Amsab ; Attia, Kader ; Baloji, Sammy ; Bartana, Yael ; Batniji, Taysir ; Benassi, Elisabetta ; Burtynsky, Edward ; Cekil, Cengiz ; Cesarco, Alejandro ; Chernysheva, Olga ; Creten, Johan ; Esber, Ninar ; et al.
Mechelen Cultural Centre, the Old Mechelen Meat Market, Museum Hof Van Busleyden, Lamot Congress and Heritage Centre, Scheppers Institute, The Academy of Fine Arts, Mechelen, 01.09 - 10.12.2012
kunstcatalogus